O efeito dos aditivos incorporador de ar e estabilizador de hidratação nas propriedades das argamassas estabilizadas - Antoniazzi, Juliana Pippi (2019)
entraining admixtures (AEA) and hydration stabilizing admixtures (HSA) modify the properties of mortar. The main effect of an AEA is increased workability, while an HSA extends the setting time. However, the full effects of these admixtures on the properties of fresh and hardened mortars are not yet well known. The aim of the present study was to evaluate the effect of the interaction of AEA and HSA with Portland cement on the properties of ready-mix mortars. For such, four papers were developed. The first evaluated the influence of mixing time, admixture content and aggregate particle size on the air-incorporation into the mortar. Thirty-six mortars were evaluated, with two fine aggregate particle sizes, three different contents of HSA (0.0%, 0.6% and 0.9%), six different contents of AEA (0.0% to 0.5%) and four mixing times (150, 210, 270 and 330 s). The second paper evaluated the setting times for different contents of HSA (0.0%, 0.6% and 0.9%) and AEA (0.0%, 0.2% and 0.4%) employed with two types of cement (F and Z). Papers 3 and 4 respectively studied the properties of fresh and hardened ready-mix mortars with different admixture contents (described in paper 2) and the analysis times. The air entrained content, consistency index, exudation and rheological parameters (squeeze flow and rheometry) were evaluated at five times of use (0, 24, 36, 48 and 72 h). Mechanical strength, degree of hydration, permeability and porosity were determined at 7, 28 and 42 days. The results indicate the stabilization of air incorporation for the mixing time of 270 s and AIA content between 0.3% and 0.4%. Mixing time influenced air incorporation only in mortars with higher contents of AEA, contrary to the effect exerted by aggregate particle size. The setting times of cement Z combined with HSA were increased compared to cement F, demonstrating the influence of cement type and admixture content. The AEA contributed to the delay in the onset of setting time, while also reducing exudation, consistency, yield stress and the elastic component of the mortars, increasing displacement under compression. The fresh state properties were influenced by admixture use and content, with the best performance of AEA soon after mixing (0 h) and HSA throughout the storage duration. In the hardened state, AEA led to a reduction in mechanical strength and provided a higher degree of mortar hydration, while HSA decreased the formation of hydrated compounds at all ages. The porosity generated by each admixture exhibited distinct characteristics and may have been influenced by the effects of the fast carbonation found in mortars with the combination of admixtures, which may exert a negative effect on the coating.